Building RESTful web services with Spring 5 : leverage the power of Spring 5.0, Java SE 9, and Spring Boot 2.0 - Raman, Raja CSP; Dewailly, Ludovic (Packt Publishing, 2018)
Find out how to implement the REST architecture to build resilient software in Java with the help of the Spring 5.0 framework. About This Book Follow best practices and explore techniques such as clustering and caching to achieve a reactive, scalable web service, Leverage the Spring Framework to quickly implement RESTful endpoints, Learn to implement a client library for a RESTful web service using the Spring Framework along with the new front end framework. Who This Book Is For This book is intended for those who want to learn to build RESTful web services with the latest Spring 5.0 Framework. To make best use of the code samples included in the book, you should have a basic knowledge of the Java language. Previous experience with the Spring Framework would also help you get up and running quickly. What You Will Learn Deep dive into the principles behind REST Expose CRUD operations through RESTful endpoints with the Spring Framework Devise response formats and error handling strategies, offering a consistent and flexible structure to simplify integration for service consumers Follow the best approaches for dealing with a service's evolution while maintaining backward compatibility Understand techniques to secure web services Comply with the best ways to test RESTful web services, including tips for load testing Optimise and scale web services using techniques such as caching and clustering In Detail REST is an architectural style that tackles the challenges of building scalable web services. In today's connected world, APIs have taken a central role on the web. APIs provide the fabric through which systems interact, and REST has become synonymous with APIs. The depth, breadth, and ease of use of Spring makes it one of the most attractive frameworks in the Java ecosystem. Marrying the two technologies is therefore a very natural choice. This book takes you through the design of RESTful web services and leverages the Spring Framework to implement these services. Starting from the basics of the philosophy behind REST, you'll go through the steps of designing and implementing an enterprise-grade RESTful web service. Taking a practical approach, each chapter provides code samples that you can apply to your own circumstances. This second edition brings forth the power of the latest Spring 5.0 release, working with MVC built-in as well as the front end framework. It then goes beyond the use of Spring to explores approaches to tackle resilience, securit ...